Implementación del proceso contable a "Telecentro Saraguro" de la ciudad de Saraguro de la provincia de Loja. Periodo julio - septiembre del 2016. - Quishpe Lozano, Mariana de Jesús (2018)
This thesis work, has been developed giving full compliance with Regulation of Academic Board of the National University of Loja and was carried out in order to apply the knowledge acquired during academic training in addition I provide a contribution to TELECENTRO SARAGURO with implementation of the Commercial Accounting and its Financial State respectively according to the rules and legal provisions and as a prerequisite to choose the degree of Accounting Engineering and Auditor Auditing Public Accountant. In compliance with the stated objectives, the application of commercial accounting was started with the collection of the information and source documents of Telecentro Saraguro, which was collected from the purchase and sales receipts for the systematization, analysis and processing of the data, that allows obtaining accurate and timely information, which served as the basis for designing the different accounting records, the Plan and Manual of accounts was established according to the needs and characteristics of the company, then the accounting process was organized, which It started with the lifting of the Initial Inventory and the Initial Situation Statement, concluding the accounting process with the obtaining of the Financial Statements. It is concluded that with the application of commercial accounting, based on accounting and tax principles and rules, real, timely and reliable financial statements can be obtained, which will make it possible to recommend to the owner, take advantage of and continue with the implementation of commercial accounting, this way you can establish a control for a normal operation with real Financial Statements, reliable, timely and above all comparable, the best decisions will be made for profit and growth of the company.